Development of Workshop Modules Using Agile Scrum Models in ERP Systems at PT Surya Data Infokreasi - Irmawati, Risa; Prasetyo, Junaedi Adi; Wibowo, Galih Hendra; Kristanto, Sepyan Purnama; Hakim, Lutfi (JURNAL JARTEL: Jurnal Jaringan Telekomunikasi, 2024)
This research aims to develop a workshop module using the Agile Scrum development model in the web-based ERP system at PT. Surya Data Infokreasi. PT ABC, a frozen goods shipping company, requires effective management of vehicle assets, including spare parts, tires, and cooling boxes. Currently, their ERP system lacks an adequate module for these needs. Agile Scrum was chosen for its suitability in developing large-scale, modular ERP systems. The workshop module includes features for service requests, spare parts requests, truck spare parts usage, and truck spare parts reports. Functionality testing was conducted using the User Acceptance Testing (UAT) method. Results show that out of 43 test cases, 36 were successful (84%), 6 failed (14%), and 1 passed with exceptions (2%). The system’s success in meeting user needs reached 84%, indicating that the workshop module can help PT ABC manage vehicle assets and workshop operations more effectively. The conclusion is that Agile Scrum proved effective in developing a system that meets specific user needs. The implementation of this module is expected to increase the efficiency of workshop management at PT ABC and provide accurate data for decision-making regarding vehicle assets